ФОРМИРОВАНИЕ КОНСТРУКТИВНЫХ СПОСОБОВ РЕАГИРОВАНИЯ В КОНФЛИКТНЫХ СИТУАЦИЯХ - Бердиева, Г.Д. (SCIENCE and SOCIETY, 2020)
This article discusses situations that arise in conflict situations, constructive methods of communication in conflict situations, the results of their study and basic concepts.
Keywords: conflict; conflict situations; social group; internal conflict; constructive method; emotional stability; self-management; behavior; social norm; assimilation; model; role-playing games; interactive training; psychological education